Uso de maíz forrajero hidropónico en la alimentación del ganado vacuno en ecuador - Marmolejo Dicado, Aron Felipe (2023)
An alternative method of providing protein to ruminants such as cattle is through hydroponically grown corn fodder (HMF). The objective was to describe how hydroponically grown forage corn is used to feed livestock in Ecuador. The inferences made are as follows: The nutritional quality of hydroponic green corn forage provides dry matter (on a dry basis) 86.60 - 90.93%, crude protein 9.78 - 19%, crude fiber 5.40 - 25, 10%, total digestible nutrients 71.87 - 80.81%, Metabolizable Energy of 3216 kcal/kg, its digestibility ranges between 83-90%, contains carotene 24.9 IU/kg, p. p. m), Zinc 35 p.p. In addition, it is an important source of non-structural carbohydrates that will quickly improve animal performance, whether in maintaining body conditions or milk production; The productive parameters of Corn Hydroponic Green Forage are better when grown at 75% of the nutrient level; Forage corn is a good alternative when it comes to complementing the ruminant's diet because it provides energy that favors the stimulation of the rumen metabolism; due to the fact that the aerial part of the corn seedling stands out for having higher nutritional levels.